Radiological Imaging of Gastro-Entero-Pancreatic Neuroendocrine Tumors. The Review of Current Literature Emphasizing the Diagnostic Value of Chosen Imaging Methods - Półtorak-Szymczak, Gabriela; Budlewski, Tadeusz; Furmanek, Mariusz Ireneusz; Wierzba, Waldemar; Sklinda, Katarzyna; Walecki, Jerzy; Mruk, Bartosz (Frontiers in Oncology, 2021)
Imaging of neuroendocrine neoplasms (NENs) poses a diagnostic challenge, mostly because of their heterogeneity and relatively long- term growth. Information obtained using radiological imaging simplifies the most appropriate treatment method. Moreover, radiological imaging methods play an important role in the assessment of metastatic lesions, especially in the liver, and tumor response to treatment. This article reviews the current imaging modalities used in the diagnosis of NEN with emphasis on the strengths and limitations of each modality.